PENGARUH SAAT PEMUPUKAN UREA PADA SISTEM GANDA AZOLLA‐PADI SAWAH TERHADAP N‐KAPITAL TANAH DAN HASIL PADI DI ENTISOL - Sudadi Sudadi; Sumarno Sumarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : Fertilizing Time Effect of Urea in Dual System Azolla‐Rice Paddy to Soil Capital Nitrogen and Rice Yield on Entisol. The purposed of research was to study the effect of urea use in dual system azolla‐rice paddy to soil capital nitrogen  and rice yield on Entisol. Research  was conducted  on rice paddy field at Colomadu,  Karanganyar  district, Central Java. The experiment  arranged in single factor randomized completely block design (RCBD), with eight treatments says D1  (azolla + 100 kg urea /ha at 0 day after planting‐dap), D2 (azolla + 100 kg urea /ha at 30 dap), D3 (azolla + 100 kg urea /ha at 60 dap), D4 (azolla + 50 kg urea /ha at 0 and 30 dap), D5 (azolla + 50 kg urea /ha at 30 and 60 dap), D6  (azolla + 50 kg urea /ha at 0 and 60 dap), D7  (control treatment ‐ without azolla nor NPK fertilizer), and D8  (lokal farmer treatment ‐ 250 kg urea /ha split three times, 50 kg/ha at 0 dap, 100 kg/ha at 30 dap and 100 kg/ha at 60 dap). Azolla inoculums spreaded 7 dap at rates 500 g/m2. Variables observed were soil capital nitrogen, soil total‐N, tissue total‐N, soil organic matter content and rice yield. Data taken was analyzed  with anova and followed with Duncan Multiple Range Test (DMRT) at 5 %  level of significant. The results show that the use of urea in dual  system  azolla‐rice  paddy  increase  soil  capital  nitrogen,  soil  total‐N,  tissue  total‐N,  soil organic matter content and rice yield at Entisol. The highest soil capital nitrogen (0,953 kg/ha) and rice yield (8 ton/ha) were taken from the treatment of  D8 and D3 respectively.Keywords: azolla‐rice paddy, rice yield, soil capital nitrogen, Urea